2021
DOI: 10.1021/acs.bioconjchem.1c00286
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion of Unexpected Thiol States Affects the Stability, Structure, and Dynamics of Antibody Engineered for Site-Specific Conjugation

Abstract: Antibody–drug conjugates have become one of the most actively developed classes of drugs in recent years. Their great potential comes from combining the strengths of large and small molecule therapeutics: the exquisite specificity of antibodies and the highly potent nature of cytotoxic compounds. More recently, the approach of engineering antibody–drug conjugate scaffolds to achieve highly controlled drug to antibody ratios has focused on substituting or inserting cysteines to facilitate site-specific conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Initial characterization across four antibody intermediates revealed that the inserted cysteine at position C239 could adopt several, distinct thiol states during manufacture: free thiol (2xSH), cysteinylated (1x/2x Cys), and an additional disulfide bond between both C239i residues (iDSB) (Figure A, C). These findings correlate with those of Orozco et al and Cao et al (2xSH and iDSB variants discussed only). Orozco et al used high resolution tandem mass spectrometry and the ensuing unique peptide fragmentation patterns to confirm that the additional disulfide bond was configured similarly to the canonical mAb interchain disulfide bridgea heavy–heavy link at equivalent sites (C239) of each chain.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Initial characterization across four antibody intermediates revealed that the inserted cysteine at position C239 could adopt several, distinct thiol states during manufacture: free thiol (2xSH), cysteinylated (1x/2x Cys), and an additional disulfide bond between both C239i residues (iDSB) (Figure A, C). These findings correlate with those of Orozco et al and Cao et al (2xSH and iDSB variants discussed only). Orozco et al used high resolution tandem mass spectrometry and the ensuing unique peptide fragmentation patterns to confirm that the additional disulfide bond was configured similarly to the canonical mAb interchain disulfide bridgea heavy–heavy link at equivalent sites (C239) of each chain.…”
Section: Resultssupporting
confidence: 92%
“…Rapid formation of iDSB within 24 h at 37 °C after deglycosylation further supports the hypothesis that a steric constraint must be overcome to form the iDSB and is consistent with previous findings (Figure S6). 26 Why the level of iDSB remains relatively constant (ca. ∼ 20%) during the fed-batch process remains unclear.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data corroborate the findings of the DSC analysis and indicate that TetraDVP conjugates may have increased stability compared to conjugates made via rebridging of two cysteine residues. Overall, it should be noted that the modest destabilising effects caused by both DVP and TetraDVP conjugation compare favourably to those caused by other clinically successful site-selective antibody modification approaches or mutations in the C H 2 domain, 53–55 showcasing the merits of this form of cysteine modification.…”
Section: Resultsmentioning
confidence: 94%